Efeito da estrutura de líquidos iônicos derivados do imidazol no aquecimento de solventes moleculares sob irradiação com ultrassom - Krüger, Nícolas (2019)
In this work, the heating profile of water, dimethyl sulfoxide (DMSO), acetonitrile (CH3CN) and ethanol (EtOH) and their solutions doped with imidazolium based ionic liquids (ILs) mono- (CnMIMBr, n = 4,6,8,10,12,14, and 16) and dicationic (Di-CnMIMBr n = 4,6,8 and 10), analogue ILs with BF4 anion (CnMIMBr, n = 4,8 and 14) and sodium bromide (NaBr) and sodium acetate (CH3CO2Na) were evaluated under ultrasound irradiation. Results showed that water and DMSO have a linear heating profile while CH3CN and EtOH follow a logarithmic profile. In general, the doped ILs solution warmed up a little faster than pure solvents, showing that the cationic moiety of ILs did not caused notable changes in the solvents heating profile. The concentration of ILs and the consequent dissociation effects of that were not observed either the experimental conditions tested. Addition of NaBr and CH3CO2Na changed the heating profile of ethanol, resulting in a linear profile. In addition, our results confirmed that experimental parameters such as amplitude of irradiation and volume of solution change significantly the heating profile of solvents. Finally, the heating profile of solvent and ILs doped solvent under conventional heating and stirring (silent experiments) showed that under ultrasound frequency, the cavitation process makes the heating faster and efficient. The dissipated power determination reflected more the heating profile than the heat capacity of solvent indicating that the heating rate in US reveals the cavitation effects in that medium. Results are important because they showed that the catalytic effects of ILs in chemical reactions or solvent effects in micro extraction processes under US irradiation can be retained without raising the temperature and without decomposition of ILs or products.